Re-starting smoking in the postpartum period after receiving a smoking cessation intervention: a systematic review - Jones, Matthew; Lewis, Sarah; Parrott, Steve; Wormall, Stephen; Coleman, Tim (Wiley, 2016)
Aims: In pregnant smoking cessation trial participants, to estimate (1) among women abstinent at the end of pregnancy, the proportion who re-start smoking at time-points afterwards (primary analysis) and (2) among all trial participants, the proportion smoking at the end of pregnancy and at selected time-points during the postpartum period (secondary analysis). Methods: Trials identified from two Cochrane reviews plus searches of Medline and EMBASE. Twenty-seven trials were included. The included trials were randomized or quasi-randomized trials of within-pregnancy cessation interventions given to smokers who reported abstinence both at end of pregnancy and at one or more defined time-points after birth. Outcomes were validated biochemically and self-reported continuous abstinence from smoking and 7-day point prevalence abstinence. The primary random-effects meta-analysis used longitudinal data to estimate mean pooled proportions of re-starting smoking; a secondary analysis used cross-sectional data to estimate the mean proportions smoking at different postpartum time-points. Subgroup analyses were performed on biochemically validated abstinence. Results: The pooled mean proportion re-starting at 6 months postpartum was 43% [95% confidence interval (CI) = 16–72%, I2 = 96.7%] (11 trials, 571 abstinent women). The pooled mean proportion smoking at the end of pregnancy was 87% (95% CI = 84–90%, I2 = 93.2%) and 94% (95% CI = 92–96%, I2 = 88%) at 6 months postpartum (23 trials, 9262 trial participants). Findings were similar when using biochemically validated abstinence. Conclusions: In clinical trials of smoking cessation interventions during pregnancy only 13% are abstinent at term. Of these, 43% re-start by 6 months postpartum.